Novel predators emit novel cues: a mechanism for prey naivety towards alien predators. Issue 1 (December 2017) - Carthey, Alexandra; Bucknall, Martin; Wierucka, Kaja; Banks, Peter
Abstract Detecting enemies is crucial for survival and a trait that develops over an evolutionary timeframe. Introduced species disrupt coevolved systems of communication and detection in their new ranges, often leading to devastating impacts. The classic example is prey naivety towards alien predators, whereby prey fail to recognise a new predator. Yet exactly why native prey fail to recognise alien predators remains puzzling. Naivety theory predicts that it is because novel predators emit novel cues. Distantly related animals have distinct evolutionary histories, physiologies and ecologies, predicting they will emit different cues. Yet it also possible that all predators emit similar cues because they are carnivorous. We investigate whether odour cues differ between placental and marsupial carnivores in Australia, where native prey experienced only marsupial mammal predation until 4000 years ago. We compared volatile chemical profiles of urine, scats and bedding from four placental and three marsupial predators. Chemical profiles showed little overlap between placental and marsupial carnivores across all odour types, suggesting that cue novelty is a plausible mechanism for prey naivety towards alien predators. Our results also suggest a role for olfactory cues to complement visual appearance and vocalisations as biologically meaningful ways to differentiate species.